Application of fe‐impregnated biochar from cattle manure for removing pentavalent antimony from aqueous solution - Park, Seong Jik; Lee, Yeon Jin; Kang, Jin Kyu; Lee, Jechan; Lee, Chang Gu (Applied Sciences (Switzerland), 2021)
This study assessed the applicability of Fe‐impregnated biochar derived from cattle manure (Fe‐CMB) as an adsorbent for removing Sb(V) from aqueous solutions and investigated the Sb(V) adsorption mechanism. Fe‐CMB was mainly composed of C, O, Cl, Fe, Ca, and P, and the adsorption of Sb(V) onto Fe‐CMB was identified using an energy dispersive spectrometer and Fourier transform infrared spectroscopy. Sb(V) adsorption reached equilibrium within 6 h, and the Sb(V) adsorption data as a function of time were well described by the pseudo‐second‐order model. The Langmuir isotherm model fit the equilibrium data better than the Freundlich model. The maximum adsorption capacity of Fe‐CMB for Sb(V) obtained from the Langmuir model was 58.3 mg/g. Thermodynamic analysis of Sb(V) adsorption by Fe‐CMB indicated that the adsorption process was exothermic and spontaneous. The Sb(V) removal percentage increased with the Fe‐ CMB dose, which achieved a removal of 98.5% at 10.0 g/L Fe‐CMB. Increasing the solution pH from 3 to 11 slightly reduced Sb(V) adsorption by 6.5%. The inhibitory effect of anions on Sb(V) adsorption followed the order: Cl− ≈ NO3− < SO42− < HCO3− < PO43−.
Keywords: Adsorption; Antimony; Biochar; Cattle manure; Fe impregnation; Removal